Green Investment and Sustainable Economic Growth: A Comparative Study of Singapore and Indonesia - nurul suhaila; Adnan Kapau Gani; Adaline Aleena (IJED: International Journal of Economy Development Research, 2026)
Green investment has become a strategic instrument for promoting sustainable economic growth in the era of climate change, environmental degradation, and global sustainability commitments. This article examines the role of green investment in supporting sustainable economic growth through a comparative study of Singapore and Indonesia. Singapore represents a highly developed economy with strong financial governance, advanced sustainable finance regulation, and a clear national agenda through the Singapore Green Plan 2030. Indonesia, on the other hand, represents a large emerging economy with abundant natural resources, high development needs, and growing sustainable finance policies, including the Taxonomy for Indonesian Sustainable Finance. Using a qualitative-comparative approach based on policy analysis and literature review, this study explores how both countries mobilize green investment to support low-carbon transition, renewable energy, green finance, and sustainable development. The findings show that Singapore’s strength lies in its role as a regional green finance hub, regulatory readiness, and institutional capacity, while Indonesia’s strength lies in its large-scale green project potential, renewable energy resources, and domestic development demand. However, both countries face different challenges. Singapore faces limitations in land, energy resources, and domestic project scale, while Indonesia faces challenges related to financing gaps, regulatory coordination, fossil fuel dependence, and implementation capacity. This study concludes that green investment can accelerate sustainable economic growth when supported by strong governance, clear taxonomy, policy consistency, private-sector participation, and regional cooperation.